Critical Care of the Pediatric Burn Patient - Naber, Catherine; Sheridan, Robert (Seminars in Plastic Surgery, 2024)
Life-saving pediatric burn care is often initiated in hospitals that are not designated as a pediatric burn center. Therefore, familiarity with critical care of pediatric burn patients is crucial for physicians working in all healthcare settings equipped to care for children. Management of airway, mechanical ventilation, preservation of ideal circulatory status, and establishment of vascular access in pediatric burn patients requires many unique considerations. This article aims to summarize important principles of critical care of children with significant burn injuries for review by physicians and surgeons working in hospitals designated as a pediatric burn center and those that stabilize these patients prior to referral.
Keywords: pediatric critical care; pediatric burn care; pain control